Determinants of The Financial Crisis in Transport and Logistics Sector Companies - Maghfiroh, Ismi; Hartiyah, Sri; Adawiyah, Wiwiek Rabiatul; Pramuka, Bambang Agus; Restianto, Yanuar E. (Badan Penerbit Fakultas Ekonomi dan Bisnis Universitas Singaperbangsa Karawang, 2024)
This research begins with indications of a financial crisis in several companies that are feared to result in bankruptcy in the future. The research objective is to identify the factors that cause economic crises, including leverage, company activity, market value, sales growth, profitability, and liquidity. The research approach uses quantitative methods, with the population in the form of annual reports of companies in the transportation and logistics sector for five periods (2018 to 2022). The research sample was determined through purposive sampling, so 20 company samples were obtained. Data analysis was carried out using logistic regression analysis with SPSS tools. The results of this study are H1 accepted with a significance value of leverage of 0.038 (sig <0.05). H2 is accepted with a significance value of activity of 0.002 (sig <0.05). H3 is accepted with a significance value of market value of 0.010 (sig <0.05). H4 is accepted with a significance value of revenue growth of 0.035 (sig < 0.05). While H5 is rejected with a significance value of profitability of 0.717 (sig > 0.05). H6 is also dismissed with a significance value of liquidity of 0.055 (sig > 0.05). Meanwhile, H7 is accepted with a significance value of 0.000 (sig < 0.05). Thus, this simultaneously shows that leverage, activity, market value, revenue growth, profitability, and liquidity have an impact on the financial crisis.